Nurses' views of infection control: an interview study - Gould, D; Ream, E (Journal of advanced nursing, 1994)
An interview study was conducted among 173 nurses in two hospitals to explore their views concerning infection risks to themselves and patients and to identify any problems they perceived in safely performing infection control precautions during routine activities. Subjects were interested in the topic of infection control and keen to perform optimally, but perceived difficulties related to lack of expert guidance whether or not they had access to an infection control nurse. In one hospital subjects identified shortages of vital equipment (gloves, appropriate handwashing agents), and this was corroborated on a checklist used independently to document the availability of resources. When the opinions of nurses working in intensive care, surgical and medical units were compared, few differences emerged other than those explained by variation in supplies of equipment, except that intensive care unit nurses were more likely to rate their patients and themselves as particularly at risk of infection, Nurses who had been qualified longer, with more than 3 years experience in their specialty, were more conscious of infection risks.